Is the US Consumer Credit Asymmetric?. (24th June 2015) - Kumar, Saten
Abstract: We investigate the existence of any asymmetric effects in the US consumer credit. In doing so, we utilize the asymmetric cointegration methods proposed by Breitung (2001, 2002) and Enders and Siklos (2001). Furthermore, we tend to explore two additional dimensions in this literature. First, whether asymmetries (if any) are persistent over‐time in the credit demand model. Second, whether the Great recession contributed to any asymmetric impacts on the credit demand. Our results revealed that the long‐run relationship of consumer credit (credit, income, wealth and interest rate on personal loans) is asymmetric. While it is difficult to identify the direct sources of this asymmetric result, our intuition is that it is linked to the structural breaks in the rate of personal loans encountered in the early 1980s. Moreover, we find no strong evidence that much of the asymmetric impacts in consumer credit were experienced in the Great recession. Neither have we attained evidence that asymmetric impacts on credit demand are persistent over‐time.